2021
DOI: 10.3389/fpubh.2021.687628
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices Toward SARS-COV-2 Infection in the United Arab Emirates Population: An Online Community-Based Cross-Sectional Survey

Abstract: Population's preventive practices and self-isolation is determinantal in the prevention and mitigation. This study explored the adult population's knowledge, attitude, and practice toward COVID-19 in UAE between the 4th and 14th of April 2020. The study was a community-based, cross-sectional study using a self-administered electronic questionnaire covering five different aspects: demographics, knowledge, practice, attitude, source, and trust of information, and a patient health questionnaire (PHQ-2) for depres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…Most subjects with good knowledge had an excellent practice rate nearly 2.7 times higher than those with poor knowledge. This result is similar to the research results of other authors who think that the indirect effects of knowledge on preventive behaviors mediated by attitudes (efficacy) were significant [12], [25], [26]. Moreover, Bao-Liang Zhong said that knowledge and attitudes influence COVID-19 pandemic prevention practices [27].…”
Section: Discussionsupporting
confidence: 89%
“…Most subjects with good knowledge had an excellent practice rate nearly 2.7 times higher than those with poor knowledge. This result is similar to the research results of other authors who think that the indirect effects of knowledge on preventive behaviors mediated by attitudes (efficacy) were significant [12], [25], [26]. Moreover, Bao-Liang Zhong said that knowledge and attitudes influence COVID-19 pandemic prevention practices [27].…”
Section: Discussionsupporting
confidence: 89%
“…Alremeithi et al ( 15 ) explored the population's knowledge, attitude, and practice toward COVID-19 in the United Arab Emirates. The authors reported that the knowledge was linked with higher education, and there was a positive association between the level of education and SARS-COV-2 infection knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Such efforts contributed to more surveillance coverage, lower mortality rate, and earlier and higher vaccine availability and rate [1] , [2] , [5] , [6] . Trust in the government was reported by the population in several studies [4] , [32] , [33] . This was confirmed in a recent systematic review and meta-analysis of the acceptability of vaccination against COVID-19 and its predictors, trust in the government was a positive predictive factor of vaccination willingness in 20 surveyed countries [34] , [35] .…”
Section: Discussionmentioning
confidence: 99%